Differential Effects of Alpha 1-Adrenoceptor Antagonists on the Postsynaptic Sensitivity: Using Slice Patch-Clamp Technique for Inhibitory Postsynaptic Current in Substantia Gelatinosa Neurons From Lumbosacral Spinal Cord in Rats - Daisuke Uta; Tsuyoshi Hattori; Megumu Yoshimura (International Neurourology Journal, 2020)
Purpose Alpha1-adrenoceptors participate in improving storage symptoms of male lower urinary tract symptoms. However, the mechanism of action of these compounds remains unclear. The goal of the present study was to clarify the effect of α1- adrenoceptor antagonists on γ-aminobutyric acid (GABA)/glycine-mediated outward currents of the inhibitory postsynaptic current (IPSC) in substantia gelatinosa (SG) neurons from the lumbosacral spinal cord in rats. Methods Male adult Sprague-Dawley rats were used. Blind whole-cell patch-clamp recordings were performed in SG neurons from isolated spinal cord slice preparations. IPSCs were recorded in individual SG neurons to which naftopidil (100μM), tamsulosin (100μM), silodosin (30μM), or prazosin (10μM) were applied sequentially with intervening washout periods. Strychnine (2μM), bicuculline (10μM), or tetrodotoxin (TTX)(1μM) were added before naftopidil. Individual outward currents were analyzed. Results The bath application of naftopidil, yielded outward IPSCs in 13 of 52 SG neurons. The naftopidil response was unchanged in the presence of TTX. Regression analysis of the outward currents between the 1st and 2nd applications of naftopidil revealed a Pearson correlation coefficient of 0.996 with a line slope of 0.983. The naftopidil-induced outward current was attenuated in the presence of strychnine and/or bicuculline. The GABA/glycine-mediated outward currents induced by tamsulosin, silodosin, and prazosin were smaller than those obtained with naftopidil. Conclusions Naftopidil-induced GABA/glycine-mediated outward currents in a subset of SG neurons prepared from the L6– S1 level of rat spinal cord. The results indicated that α1-adrenoceptor antagonists, particularly naftopidil, induce neural suppression (in part) by mediating hyperpolarization. The response is associated with glycinergic and/or GABAergic neural transmission. Naftopidil may suppress the micturition reflex and improve urinary storage symptoms as a subsidiary effect resulting from hyperpolarization in SG neurons of the spinal cord.